The democratic constitution : experimentalism and interpretation - Butler, Brian E. (Chicago : The University of Chicago Press, 2018)
The Supreme Court is seen today as the ultimate arbiter of the Constitution. Once the Court has spoken, it is the duty of the citizens and their elected officials to abide by its decisions. But the conception of the Supreme Court as the final interpreter of constitutional law took hold only relatively recently. Drawing on the pragmatic ideals characterised by Charles Sanders Peirce, John Dewey, Charles Sabel, and Richard Posner. Brian E. Butler shows how this conception is inherently problematic for a healthy democracy. Butler offers an alternative democratic conception of constitutional law, 'democratic experimentalism', and applies it in a thorough reconstruction of Supreme Court cases across the centuries.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 12, 2017).
Keywords: Constitutional history -- United States; Democracy -- Philosophy; Law; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general